THE ESSENCE OF THE CONCEPT “HETEROGENEITY” - Д. І. Шеленко (Ринкова економіка: сучасна теорія і практика управління, 2018)
The processes of industrial relations that existed in different periods of development predetermine the emergence of different structures of their gradual transformation, modification and improvement have been investigated. The analysis of the formation of heterogeneity according to the periods of development of mankind has been carried out.